(untitled) (REMUNOM, 2026)
This study investigated the influence of particle size and solvent on the extraction efficiency of phenolic compounds and antimicrobial activity of bark extracts from Anacardium occidentale, Stryphnodendron adstringens, and Myrcia eximia, native to the Caatinga, Cerrado, and Amazon biomes, respectively. Extractions were performed using deionized water and 70% methanol in four particle size ranges (28, 35, 60, and 80 mesh). The levels of condensed tannins, total phenols, and flavonoids were measured, along with the antimicrobial activity against Gram-positive and Gram-negative bacterial strains. Extracts obtained with methanol showed higher yields in phenolic compounds compared to water, with Myrcia eximia showing the highest flavonoid content. Antimicrobial activity was more evident against Gram-positive bacteria (Staphylococcus aureus and Listeria monocytogenes), especially for Myrcia eximia extracts. These findings highlight the potential use of forest residues to obtain bioactive compounds with antimicrobial properties.